VizieR Online Data Catalog: The large TNO 2002 TC302 (Ortiz+, 2020) - Ortiz, J. L.; Santos-Sanz, P.; Sicardy, B.; Benedetti-Rossi, G.; Duffard, R.; Morales, N.; Braga-Ribas, F.; Fernandez-Valenzuela, E.; Nascimbeni, V.; Nardiello, D.; Carbognani, A.; Buzzi, L.; et al. (2020)
Table 1 includes the data from the astrometric monitoring runs for 2002 TC302 carried out to narrow down the shadow path uncertainty, in October, November, December 2017 and January 2018 with the Sierra Nevada 1.5m telescope (Granada, Spain) and the Calar Alto 1.2m telescope (Almeria, Spain). The astrometric catalog used for the occultation prediction was Gaia DR1. Tables 2 and 3 include, respectively, all the photometry and astrometry of 2002 TC302 analyzed, from 2014 to 2019. The astrometry was derived with respect to the Gaia DR2 catalog (Cat. I/345). (3 data files).
Keywords: Ephemerides; Minor planets; Occultations; Photometry: CCD; Positional data; Solar system